Evaluating the Pakistani-Afghan relations in the light of the United States aid to the two countries (Journal of the College of Basic Education, 2022)
The United States of America has been concerned with sponsoring the State of Pakistan and providing aid to it since its independence on August 15, 1947, and Karachi and Washington have tried to drag Afghanistan into these military alliances and pacts sponsored by the United States of America and pressure it to abandon its declaration of continued neutrality from entering it, and it is noticeable that Kabul saw that the level of The aid is less than the required level, and compared to the aid provided to its neighbor Pakistan, the Soviet Union took advantage of this gap, leaving Afghanistan in the arms of the Soviets, which took advantage of the deterioration of Pakistani-Afghan relations and the closure of the Karachi port, the only outlet for the exchange of Afghan goods, and Kabul itself was in imminent danger.